BIFIDOBACTERIUM ADOLESCENTIS FOR REDUCING THE RELEASE OF PROINFLAMMATORY CYTOKINES - MARTONI, Christopher; DAMHOLT, Anders (2025)
The present disclosure generally relates to probiotics for reducing the release of proinflammatory cytokines. In particular, the present disclosure provides a B. adolescentis that can reduce the overall pro-inflammatory cytokines in a subject such as, for example, interleukin-6 (IL-6). The present disclosure provides a method of preventing, reducing, or ameliorating the symptoms of stress and/or anxiety, in a subject in need thereof, with the B. adolescentis strain deposited as DSM29103 (Bif038). La présente invention concerne de manière générale des probiotiques servant à réduire la libération de cytokines pro-inflammatoires. Plus particulièrement, la présente invention concerne un B. adolescentis qui peut réduire les cytokines pro-inflammatoires globales chez un sujet telles que, par exemple, les interleukines 6 (IL-6). La présente divulgation concerne une méthode de prévention, de réduction ou d'amélioration des symptômes du stress et/ou de l'anxiété, chez un sujet en ayant besoin, avec la souche B. adolescentis déposée sous la forme DSM29103 (Bif038).